Bandwith enhancement metamaterial antenna based line approach - Bala, B. D. (Wiley Periodicals, 2015)
A composite right-/left-handed transmission line metamaterial antenna with enhanced bandwidth and efficiency is proposed. The antenna combines zeroth-order resonant (ZOR) and positive-order resonant (POR) modes for the bandwidth enhancement. An asymmetrical coplanar waveguide technique is used to feed the antenna and also to achieve certain degree of compactness. The overall size of the antenna is 0.32?0 × 0.38?0 × 0.012?0 (40 × 48 × 1.52 mm) at 2.4 GHz. Simulation results show that a bandwidth enhancement of 41% is obtained with the radiation efficiencies of 95 and 97% for the ZOR and POR modes, respectively. The measured impedance bandwidth shows that the antenna has potential applications for WLAN (2.39–2.45 GHz) and WiMAX (2.5–2.69 GHz) operations. The simulated and measured antenna performances in terms of return loss and the radiation patterns are presented and compared.